Perbandingan Aktivitas Antibakteri Ekstrak Etanol Dan Aseton Limbah Kulit Bawang Putih (Allium Sativum L.) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus - Aprila, Nur Amalia; Ulfa, Ade Maria; Susanti, Dwi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Skin infections are infections caused by pathogenic bacteria Staphylococcus aureus, such as acne, boils, scabies, versicolor, and wound infections. Treatment of skin infections can be done using natural ingredients, one of which is garlic skin waste (Allium sativum L.). This study aims to compare the antibacterial activity of ethanol and acetone extracts of garlic skin waste (Allium sativum L.) against Staphylococcus aureus. This study used maceration extraction method using 70% ethanol and 80% acetone solvents and antibacterial testing was carried out by disc diffusion method. The concentrations of 70% ethanol extract and 80% acetone of garlic skin waste used were 3%, 25%, 50% and 75%. The results showed 75% ethanol extract concentration with an average inhibition zone diameter of 2.96 mm, while 75% acetone extract with an average inhibition zone diameter of 1.7 mm with a weak category. The higher the concentration of ethanol and acetone extracts of garlic skin waste, the wider the inhibition zone. This study can be concluded that the antibacterial activity of ethanol extract with 75% concentration is better than the activity of acetone extract with the same concentration with p-value <0.05.